Intestinal adaptation to diabetes. Altered Na-dependent nutrient absorption in streptozocin-treated chronically diabetic rats. - Fedorak, R N (1987)
To examine the pattern and mechanisms of enhanced intestinal nutrient absorption in diabetes, we measured intestinal transport of 3-O-methylglucose (3OMG), l-alanine (ALA), and SO4 in male Lewis rats made diabetic with streptozocin. Diabetes enhanced 3OMG absorption fivefold in ileum and threefold in jejunum; ALA absorption increased twofold in ileum but not at all in jejunum; ileal SO4 transport was unaffected. Increases in 3OMG and ALA transport were due solely to increases in maximum velocity. The enhancement of ileal glucose absorption was half-maximal in 40-45 d, could be reversed by 10 d of treatment with insulin and did not result from adrenergic denervation. The density of glucose carriers per milligram brush border protein (measured as [3H]phlorizin binding sites) was not altered but there was a sixfold increase in the number of glucose-inhibitable [3H]phlorizin-binding sites in the intact epithelium. Generalized mucosal hypertrophy accounted for less than 30% of this increase. We conclude that the intestine adapts to streptozocin-induced diabetes through recruitment of additional brush border carriers for sugar, probably in the midvillus-to-crypt region.